CD64 enables TCR-dependent, MHC-independent CTL cytotoxicity of AML cells - Kapil Saxena; Shao-Hsi Hung; Esther Ryu; Yulun Chiu; Casey Bermack; Ke Pan; Chunhua Shi; Priscilla Ortiz; Shailbala Singh; Marina Y. Konopleva; Cassian Yee (Proceedings of the National Academy of Sciences, 2026)
CD8+ T cell–mediated cytotoxicity classically occurs through engagement of an alpha-beta T cell receptor (TCRαβ) with a peptide–class I major histocompatibility complex (pMHC). However, it is also known that cytotoxic CD8+ T lymphocytes (CTLs) can kill tumor cells in a pMHC-independent manner. The relative physiologic contribution and biological significance of pMHC-independent CTL killing remain unclear, and a receptor shared between CTLs and natural killer (NK) cells is generally invoked as the mechanism by which this occurs. In this study, we used acute myeloid leukemia (AML) as a model to examine mechanisms of pMHC-independent cytotoxicity and found a paradoxical TCR-dependent, MHC-independent mechanism that requires CD64. Utilizing knockouts of potential AML ligands and CTL receptors, we demonstrate that pMHC-independent cytotoxicity is a potent mechanism of CTL-mediating killing of AML cells and is largely restricted to CD64-expressing cells through an IFNγ-regulated process. Notably, we found that pMHC-independent CTL killing is not due to activation of commonly implicated NK activating receptors but rather requires an activated TCRαβ/CD3 complex. Thus, we identify a CD64-dependent, pMHC-independent, TCR-dependent mode of CTL cytotoxicity that appears highly enriched for in AML.